2023
DOI: 10.1587/elex.19.20220527
|View full text |Cite
|
Sign up to set email alerts
|

A 25Gb/s RX front-end with multi-stage linear equalizer and 3-tap speculative DFE in 65nm CMOS technology

Abstract: This work proposes a RX front-end structure, which is used for channel equalization of 25 Gb/s high-speed links. This design includes two parts, linear equalizer and decision feedback equalizer. Linear equalizer consists of the variable gain amplifier, the continuous-time linear equalizer and the output buffer, which provide 19 dB peaking gain around the Nyquist frequency. The half-rate decision feedback equalizer with one speculative tap is cascaded after the buffer to eliminate residual inter-symbol interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The data-traffic explosion driven by cloud computing, 5G networks, industrial IoT, and virtual reality has accelerated the demand for high-speed SerDes transceivers to provide massive data throughput [1,2,3,4,5,6,7,8]. Previous studies have demonstrated that four-level pulse amplitude modulation (PAM-4) is superior to non-return-to-zero (NRZ) for the 56∼112-Gb/s serial data communications due to its doubled spectral efficiency, halved Nyquist frequency, and relaxed clock speeds [9,10,11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The data-traffic explosion driven by cloud computing, 5G networks, industrial IoT, and virtual reality has accelerated the demand for high-speed SerDes transceivers to provide massive data throughput [1,2,3,4,5,6,7,8]. Previous studies have demonstrated that four-level pulse amplitude modulation (PAM-4) is superior to non-return-to-zero (NRZ) for the 56∼112-Gb/s serial data communications due to its doubled spectral efficiency, halved Nyquist frequency, and relaxed clock speeds [9,10,11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%